5(х-3)=4х-6.. -(13х+1)=-15х+ 17(х+2)-19=5(5х-0,2)-3(7х+ 0.8х+14=2-1,6х.. 2х-1=5(х+4)

крист34 крист34    1   19.08.2019 07:50    0

Ответы
fheeubeujdshebj fheeubeujdshebj  20.08.2020 11:36
Вот все решение прощение за качество
5(х-3)=4х-6.. -(13х+1)=-15х+ 17(х+2)-19=5(5х-0,2)-3(7х+ 0.8х+14=2-1,6х.. 2х-1=5(х+4)
ПОКАЗАТЬ ОТВЕТЫ
Kris15kim Kris15kim  20.08.2020 11:36
5(х-3)=4х-6
5х-15-4х+6=0
х-9=0
х=9

-(13х+1)=-15х+5
-13х-1+15х-5=0
2х-6=0
2х=6
х=3

17(х+2)-19=5(5х-0,2)-3(7х+3)
17х+34-19-25х+1+21х+9=0
13х+26=0
13х=-26
х=-2

0,8х+14=2-1,6х
0,8х+1,6х=2-14
2,4х=-12
х=-5

2х-1=5(х+4)
2х-1=5х+20
2х-5х=20+1
-3х=21
3х=-21
х=-7
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика